Efektivitas Pembelajaran Matematika Menggunakan Bahan Ajar Berbasis Integrasi Interkoneksi terhadap Peningkatan Kemampuan Berpikir Kritis Mahasiswa - Suparni Suparni (Universitas Syiah Kuala, 2018)
Thispurpose of this study was to analyze the effectiveness of Mathematics instruction employing the instructional materials based on the interconnection integration on students' critical thinking ability. This is a quasi-experimental research utilizing the pre-test post-test control group design. The subjects of this research are all students of Mathematics Education Study Program Faculty of Science and Technology UIN Sunan Kalijaga Yogyakarta who enrolled in Mathematics Learning Strategy course (48 students in experimental class and 31 students in control class). Data was collected using test and questionnaires. Data analysis was carried out by using t-test. Based on the result, it is identified that Mathematics instruction using the instructional materials based on the interconnection integration is more effective than conventional instruction to improve students critical thinking ability of Mathematics Education Study Program Faculty of Science and Technology UIN Sunan Kalijaga Yogyakarta